Hepatic caveolin-1 is enhanced in Cyp27A1/ApoE double knockout mice - Zurkinden, Line; Mansour, Yosef; Rohrbach, Beatrice; Vogt, Bruno; Mistry, Hiten D.; Escher, Genevieve (Wiley, 2016)
Sterol 27-hydroxylase (CYP27A1) is involved in bile acid synthesis and cholesterol homoeostasis. Cyp27a1(−/−)/Apolipoprotein E(−/−) double knockout mice (DKO) fed a western diet failed to develop atherosclerosis. Caveolin-1 (CAV-1), the main component of caveolae, is associated with lipid homoeostasis and has regulatory roles in vascular diseases. We hypothesized that liver CAV-1 would contribute to the athero-protective mechanism in DKO mice. Cyp27a1(+/+)/ApoE(−/−) (ApoE KO), Cyp27a1(+/−)/ApoE(−/−) (het), and DKO mice were fed a western diet for 2 months. Atherosclerotic plaque and CAV-1 protein were quantified in aortas. Hepatic Cav-1 mRNA was assessed using qPCR, CAV-1 protein by immunohistochemistry and western blotting. Total hepatic and plasma cholesterol was measured using chemiluminescence. Cholesterol efflux was performed in RAW264.7 cells, using mice plasma as acceptor. CAV-1 protein expression in aortas was increased in endothelial cells of DKO mice and negatively correlated with plaque surface (P < 0.05). In the liver, both CAV-1 protein and mRNA expression doubled in DKO, compared to ApoE KO and het mice (P < 0.001 for both) and was negatively correlated with total hepatic cholesterol (P < 0.05). Plasma from DKO, ApoE KO and het mice had the same efflux capacity. In the absence of CYP27A1, CAV-1 overexpression might have an additional athero-protective role by partly overcoming the defect in CYP27A1-mediated cholesterol efflux.